Benin's stealthy democracide: How Africa's model democracy kills itself bit by bit - Dirk Kohnert; Hans-Joachim Preuss (ZBW – Leibniz Information Centre for Economics, 2019)
A 'democratic recession' is to be observed, which is not restricted to Sub-Sahara Africa but spreads worldwide since the beginning of the 21st century. Instead of concentrating on the outward appearance of a democratic form of government, greater attention should be paid to good governance and the stealthy erosion of democratic institutions, even in formerly shining examples and African 'model democracies' like Benin and Senegal. It went along with the rise of populist new nationalism and lack of regard of the concerned for the need to defend democracy actively. The lingering process of the decline of democratic institutions is driven by increasingly poor governance and disregard for the rule of law and transparency, which has been especially pronounced in African countries since the early 2000s. On the other hand, recent examples of African social movements that successfully campaigned for a democratic renaissance in Africa and elsewhere are promising indicators of progressive social forces that counteract global trends of the resurgence of right-wing nationalism and autocratic rule. – – RÉSUMÉ : On observe une «récession démocratique» qui ne se limite pas à l'Afrique subsaharienne mais s'étend à l'échelle mondiale depuis le début du XXIe siècle. Au lieu de se concentrer sur l'apparence extérieure d'une forme de gouvernement démocratique, il faudrait accorder une plus grande attention à la bonne gouvernance et à l'érosion furtive des institutions démocratiques, même dans les exemples jadis brillants et les «démocraties modèles» africaines comme le Bénin et le Sénégal. Cela a coïncidé avec la montée d'un nouveau nationalisme populiste et le manque de vigilance des personnes concernées quant à la nécessité de défendre activement la démocratie. Le processus persistant du déclin des insti-tutions démocratiques s'explique par une gouvernance de plus en plus médiocre et le mépris de l'état de droit et de la transparence, qui se fait particulièrement sentir dans les pays africains depuis le début des années 2000. D'autre part, des exemples récents de mouve-ments sociaux africains qui ont mené avec succès une renaissance démocratique en Afrique et ailleurs sont des indicateurs prometteurs de forces sociales progressistes qui vont à l'encontre des tendances mondiales à la résurgence d'un nationalisme de droite et des ré-gimes autocratiques. ——————————————————————————————————————————————————————— ZUSAMMENFASSUNG : Es ist eine "demokratische Rezession" zu beobachten, die sich nicht nur auf Afrika südlich der Sahara beschränkt, sondern sich seit Beginn des 21. Jahrhunderts weltweit ausbreitet. Anstatt sich auf das äußere Erscheinungsbild einer demokratischen Regierungsform zu konzentrieren, sollte der verantwortungsvollen Regierungsführung und der heimlichen Erosion demokratischer Institutionen größere Aufmerksamkeit geschenkt werden, selbst in früheren Vorbildern und afrikanischen ,,Modelldemokratien“ wie Benin und Senegal. Dies geht einher mit dem Aufkommen eines populistischen neuen Nationalismus und dem mangelnden Augenmerk auf die Notwendigkeit, die Demokratie aktiv zu verteidigen. Der anhaltende Niedergang der demokratischen Institutionen ist auf eine zunehmend mangelhafte Regierungsführung und die Missachtung von Rechtsstaatlichkeit und Transparenz zurückzuführen, die in den afrikanischen Ländern seit Anfang der 2000er Jahre besonders ausgeprägt ist. Andererseits sind afrikanischer soziale Bewegungen, die sich erfolgreich für eine demokratische Renaissance in Afrika und anderswo einsetzen, vielversprechende Indikatoren für fortschrittliche soziale Kräfte, die globalen Trends des Wiederauflebens eines rechten Nationalismus und autokratischer Herrschaft entgegenwirken.
Keywords: F35; K15; K16; N47; N97; Z13; 330; Benin; Democratization; Senegal; Togo; democratic recession; social movements; governance